Effectiveness of Mindfulness-Based Cognitive Therapy on Psychological Capital, Perceived Social Support, and Learned Helplessness in Women with Psoriasis - AleKasir, Maryam; Abbasian Haddadan, Maryam (Psychology of Woman Journal, 2025)
Objective: The purpose of the present study was to examine the effectiveness of mindfulness-based cognitive therapy (MBCT) on psychological capital, perceived social support, and learned helplessness in women with psoriasis. Methods and Materials: The research method was semi-experimental, with a pretest-posttest design and a control group. The statistical population of the study included all women with psoriasis who visited counseling centers in District 5 of Tehran in 2023. The sample consisted of 30 individuals, selected through convenience sampling, and were then randomly assigned to either the experimental or control group. The experimental group received eight 90-minute sessions of MBCT, while the control group remained on a waiting list. The data collection tools included the Psychological Capital Questionnaire (Luthans, 2007), the Perceived Social Support Questionnaire (Zimet et al., 1988), and the Learned Helplessness Questionnaire (Peterson et al., 1982). Content validity was used to assess the validity of the instruments, with the questionnaires being approved by relevant experts. Data analysis was performed using SPSS-v26 software, with both descriptive and inferential statistics (analysis of covariance) being employed. Findings: The results indicated that mindfulness-based cognitive therapy significantly increased psychological capital and its components in women with psoriasis. MBCT also led to improvements in perceived social support and its components. Furthermore, the results revealed that MBCT effectively reduced learned helplessness in women with psoriasis. The Conclusion: The findings suggest that mindfulness-based cognitive therapy has a significant positive impact on psychological capital, perceived social support, and learned helplessness in women with psoriasis.